Lactobacillus mucosae exerted different antiviral effects on respiratory syncytial virus infection in mice - Wang, Qianwen; Fang, Zhifeng; Li, Lingzhi; Wang, Hongchao; Zhu, Jinlin; Zhang, Pinghu; Lee, Yuan-kun; Zhao, Jianxin; Zhang, Hao; Lu, Wenwei; Chen, Wei (Frontiers in Microbiology, 2022)
Respiratory syncytial virus (RSV) infection is a constant threat to the health of young children, and this is mainly attributed to the lack of effective prevention strategies. This study aimed to determine whether Lactobacillus (L.) mucosae, a potential probiotic, could protect against respiratory viral infection in a mouse model. Naive 3–4-week-old BALB/c mice were orally administered with three L. mucosae strains (2.5 × 108 CFU/mouse) 7 days before RSV infection (105 TCID50/mouse). Results showed that all three strains inhibited RSV replication and reduced the proportions of inflammatory cells, including granulocytes and monocytes in the blood. The L. mucosae M104R01L3 treatment maintained stable weight in mice and increased interferon (IFN)-β and tumor necrosis factor (TNF)-α levels. The L. mucosae DCC1HL5 treatment increased interleukin (IL)-1β and IL-10 levels. Moreover, the M104R01L3 and DCC1HL5 strains increased the proportions of Akkermansia, Alistipes, and Anaeroplasma which contributed to the advantageous modulation of the gut microbiota. Besides, L. mucosae affected the gut levels of short-chain fatty acids (SCFAs) that are important for the antiviral response. L. mucosae 1,025 increased acetate, propionate, and butyrate levels, whereas L. mucosae M104R01L3 increased the level of acetate in the gut. L. mucosae M104R01L3 may protect against viral infection by upregulating the IFN-β levels in the lungs and its antiviral effect may be related to the increase of acetate levels in the gut. In conclusion, the three L. mucosae strains exerted antiviral effects against RSV infection by differentially regulating immune responses and intestinal micro-ecological balance. This study can provide a reference for studying the mechanisms underlying the antiviral effects of L. mucosae.